2018
DOI: 10.1007/s10238-018-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological value of programmed cell death 1 (PD-1) and programmed cell death ligand 1 (PD-L1) expression in synovium of patients with rheumatoid arthritis

Abstract: The etiology of rheumatoid arthritis (RA) is thought to involve dysfunction of the programmed cell death 1/programmed cell death ligand 1 (PD-1/PD-L1) pathway; PD-1 negatively regulates autoimmunity by interacting with its ligand, PD-L1. We therefore investigated PD-1/PD-L1 expression in synovial tissue of patients with RA. We immunohistochemically stained synovial specimens from 51 patients with RA and assessed the association between PD-1/PD-L1 expression and rheumatoid factor (RF), the total count of infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The engagement of Tregs with autoreactive B cells via the PD-1/L1 inhibitory axis can trigger B cells apoptosis and inhibit the production of autoantibody ( 22 ). In patients with RA, lymphocytes infiltrating the synovium commonly express PD-1, the synovial lining cells express PD-L1, and the number of PD-1-positive lymphocytes was significantly larger in RA than in osteoarthritis ( 23 ). In addition, the PD-L1 expression on synovial lining cells was positively related to the number of infiltrating T cells and Krenn’s synovitis score ( 23 ), indicating an important role of PD-1 pathway in RA.…”
Section: Relationship Between Immune Checkpoints and Aidmentioning
confidence: 99%
See 1 more Smart Citation
“…The engagement of Tregs with autoreactive B cells via the PD-1/L1 inhibitory axis can trigger B cells apoptosis and inhibit the production of autoantibody ( 22 ). In patients with RA, lymphocytes infiltrating the synovium commonly express PD-1, the synovial lining cells express PD-L1, and the number of PD-1-positive lymphocytes was significantly larger in RA than in osteoarthritis ( 23 ). In addition, the PD-L1 expression on synovial lining cells was positively related to the number of infiltrating T cells and Krenn’s synovitis score ( 23 ), indicating an important role of PD-1 pathway in RA.…”
Section: Relationship Between Immune Checkpoints and Aidmentioning
confidence: 99%
“…In patients with RA, lymphocytes infiltrating the synovium commonly express PD-1, the synovial lining cells express PD-L1, and the number of PD-1-positive lymphocytes was significantly larger in RA than in osteoarthritis ( 23 ). In addition, the PD-L1 expression on synovial lining cells was positively related to the number of infiltrating T cells and Krenn’s synovitis score ( 23 ), indicating an important role of PD-1 pathway in RA. Notably, in non-obese diabetic mice, both anti–CTLA-4 and anti–PD-1 treatment can prevent anergy induction in islet antigen–specific T cells, but only PD-1/L1 blockade can reverse experimentally induced anergy, indicating a unique function for PD-1 signaling in maintaining T cells anergy ( 24 ).…”
Section: Relationship Between Immune Checkpoints and Aidmentioning
confidence: 99%
“…In patients with chronic RA, the plasma level of sPD-1 was also significantly higher than in healthy volunteers [37]. Studies observed that the expression of sPD-1/ sPD-L1 increased in serum of RA patients, and the expression of mPD-1/mPD-L1 also increased in synovial tissue and spleen [38,39]. CD4+T cells were cocultured with synovial fluid mononuclear cells in vitro, and the addition of high concentration of sPD-L1 fusion protein could promote the proliferation of T cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…A number of RA studies have reported PD-1 expression on T cells infiltrating the synovial membrane, synovial fluid, and peripheral blood, as well as the PD-L1 expression on the synovial tissue and synovial fluid [ 108 , 109 , 110 ]. Higher PD-L1 expression on the synovial lining cells was associated with an RF positive state, more infiltrating CD3-positive T cells, higher CRP, and more pronounced synovitis in RA [ 109 ].…”
Section: Immune Checkpoints Are Promising Targets For Targeted Immuno...mentioning
confidence: 99%